Possessing the Past : Trauma, Imagination, and Memory in Post-Plantation Southern Literature - Hinrichsen, Lisa, 1978- (Book collections on Project MUSE., 2015)
Employing recent theories of memory from multiple areas of study, Possessing the Past illuminates the tangled relationships among trauma, fantasy, and the public sphere, and their impact on the "South" in imagination and in reality. Focusing on the roles that narrative and fantasy play in creating a sense of regional distinctiveness, Lisa Hinrichsen brings a wealth of critical scholarship to her consideration of memory and southern literature. Hinrichsen's nuanced readings of a diverse group of southern authors, including William Faulkner, Roberto Fernández, Erna Brodber, Monique Truong, and Katharine Du Pre Lumpkin, offer new ways of conceptualizing memory, place, and history. She unravels southern literature's critical confrontation with the region's history through complex systems of remembrance and erasure, and she traces how fantasy mediates trauma and adjudicates identity. Expansive in its psychoanalytical approach, her work explores issues of law, testimony, and social justice; the role of nostalgic fantasies of gentility at midcentury; the relationship between white empathy and social fantasy; the resemblance of regional patterns of disavowal to national ideologies of forgetting in Vietnam-era fiction; and the impact of contemporary multicultural literature on memory and community. Possessing the Past broadens the theoretical framework used to conceptualize memory and trauma, while grounding traumatic testimony in the specifics of time and place amply offered by southern literature. It provides new readings of an array of southern writers and deepens our understanding of the continuing importance of history, memory, and fantasy in the literature of the U.S. South.--Amazon.com.